First record of Rachiplusia nu (Lepidoptera: Noctuidae) as host of the egg parasitoid Trichogramma bruni (Hymenoptera: Trichogrammatidae) - Valverde, Liliana (2014)
This is the first report of this important pest as host of this egg parasitoid. The association was registered in soybean crops in Tucumán, Argentina.